The Impact of Knowledge Management on Work Performance through the Employees’ Competence: A Case Study of “MP” Bank - Muhammad Annasrudin Nasikhin; Nevi Danila (STIE Perbanas Surabaya, 2017)
Since it was established in 2003 until 2014, the “MP” bank had never provided its human resources development training. As a result, it decreased its employees’ performance which ultimately gave a bad impact on the bank. This was a serious concern for the management in 2015. This study aimed to determine and analyze the impact of knowledge management variables consisting of socialization, externalization, combination, and Internalisation on the employees performance indirectly through their competence. The path analysis was used to determine the indirect impact of knowledge management on the wmployess’ performance, with the samples of 140 people. The data analysis and hypothesis testing proved that knowledge management had significant effect on the employees performance indirectly through the employees competence. The R-square of socialization, externalization, combination, and internalisation of the employees competence were 70.5%; and the R-square of competence variable to the performance was 52%. This showed that knowledge management played an important role in improving the employees performance through their competence. It implies that the bank needs to provide in-house training for its employees resource development because only relying on the quality the employees get from the college was not enough